STUDI EVALUATIF PENERAPAN PRINSIP KONTINUITAS DALAM SEBARAN MATA KULIAH PBA STIT HIDAYATUNNAJAH BEKASI (Al-Muradif: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to evaluate the application of the principle of continuity in the distribution of courses of the Arabic Language Education Study Program (PBA) STIT Hidayatunnajah Bekasi. The analysis is focused on three main aspects according to Tyler, namely sustainability, sequencing and integration. The research uses a qualitative descriptive approach through the analysis of curriculum documents and interviews with the teaching lecturer. The results of the study show that the principle of continuity has been seen in several groups of subjects, especially mahārah and qawā'id. However, it was found that there was a missynchronization of the course order, especially between Nahwu-Sharaf, late placement of Psycholinguistics, long gaps between Kitābah levels, and an unbalanced credit load in semester VII. This study recommends curriculum restructuring to be more sustainable across semesters and across courses. These results contribute to strengthening the continuity-based PBA curriculum design.